Dominican Republic : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Dominican Republic. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2019)
This 2019 Article IV Consultation with the Dominican Republic discusses that the economy rebounded to a record high growth of 7 percent in 2018, with the positive momentum carrying into early 2019. The strong economic and policy performance has strengthened resilience to downside risks, but vulnerabilities remain. The fiscal position is under moderate sustainability and affordability pressures; key structural bottlenecks have not been addressed; and social outcomes can be further strengthened. Upcoming elections in 2020 are likely to dominate the near-term policy landscape. The outlook is favorable, with growth moderating to potential, inflation picking up toward target with fading supply shocks, and the external position normalizing. Risks are moderate and balanced: on the upside, solid income and credit growth could sustain domestic demand, while on the downside external risks are building up. Tighter fiscal policies are warranted by demand, sustainability and affordability considerations. A frontloaded adjustment, anchored on widening the tax base and mindful of the distributional effects of the adjustment measures, would help reverse the upward debt dynamics.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet